2019
DOI: 10.1038/s41598-019-38616-5
|View full text |Cite
|
Sign up to set email alerts
|

Cilioretinal Arteries and Cilioretinal Veins in Eyes with Pathologic Myopia

Abstract: We investigated the clinical characteristics of cilioretinal arteries (CAs) and cilioretinal veins (CVs) in eyes with pathologic myopia. Ninety-five eyes with pathologic myopia and CAs were studied. The retrobulbar vessels from which the CAs originated were identified by indocyanine green angiography (ICGA). The results showed that 114 CAs were identified in the 95 eyes. ICGA showed that 60% of the CAs branched directly off the short posterior ciliary arteries (SPCAs) and 40% originated from the Zinn-Haller ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…There is already growing interest in analyzing the chorioretinal diseases in relation to scleral vessels. In high myopia, Ishida et al 8 and Watanabe et al 17 showed CNV next to the location of the scleral vessels. Moriyama et al 18 showed displaced PCAs entrance in the choroid around the boundaries of the staphyloma.…”
Section: Discussionmentioning
confidence: 98%
“…There is already growing interest in analyzing the chorioretinal diseases in relation to scleral vessels. In high myopia, Ishida et al 8 and Watanabe et al 17 showed CNV next to the location of the scleral vessels. Moriyama et al 18 showed displaced PCAs entrance in the choroid around the boundaries of the staphyloma.…”
Section: Discussionmentioning
confidence: 98%
“…There is already growing interest in analyzing the chorioretinal diseases in relation to scleral vessels. In high myopia, Ishida et al 8 and Watanabe et al 17 showed CNV next to the location of the scleral vessels. Moriyama et al 18 showed displaced PCAs entrance in the choroid around the boundaries of the staphyloma.…”
Section: Discussionmentioning
confidence: 98%
“… 8 10 Studies have attempted to uncover the role of cilioretinal arteries in high myopia. For example, Watanabe et al 11 demonstrated the derivation of cilioretinal arteries in high myopia, including short posterior ciliary arteries and Zinn–Haller arterial rings. Our group has previously proposed a photographic classification system of the cilioretinal artery in high myopia that is clinically relevant to visual acuity (VA).…”
mentioning
confidence: 99%